(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of continuous multifunctions defined between an ideal topological space and a bitopological space, called upper weakly τ^α(σ_1,σ_2)-continuous multifunctions and lower weakly τ^α(σ_1,σ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper weakly τ^α(σ_1,σ_2)-continuous multifunctions and lower weakly τ^α(σ_1,σ_2)-continuous multifunctions are considered.